Legislating Transit "Coopetition": Privatization and Planning Devolution in Germany. Issue 1 (January 2016) - Koch, Martha; Newmark, Gregory L.
Market liberalization is often heralded as a solution for unprofitable public services; however, such liberalization can result in competitive practices that harm service quality, particularly for public transit. Germany experienced this detrimental competition when its transit privatization initially led to operators' instituting business practices designed to keep riders on their portion of the network and degrading the overall user experience and driving down systemwide ridership and revenue. To repair the system fragmentation and revive their profits, the operators banded together in cooperative regional transportation alliances known as Verkehrsverbünde. Composed of both public and private transit providers as well as local authorities, Verkehrsverbünde coordinate transit planning, operations, and fare structures to provide customers with a unified, accessible, and efficient transportation system. From the inception of the first Verkehrsverbund in 1965 through the early 1990s, 11 of Germany's largest metropolitan areas adopted this model and realized increases in ridership and revenue. Although the benefits of the Verkehrsverbund model have been considered elsewhere, the critical role of Germany's evolving legal framework in encouraging Verkehrsverbünde has not been explored. This research finds that federal legislation passed in 1993 provided fertile ground for such cooperative competition— or "coopetition"—to flourish. The legislation both advanced transit privatization and devolved planning, financing, and administrative responsibilities to state governments. In response, German states actively created new alliances to more than quintuple the number of Verkehrsverbünde. Today nearly all public transportation operations in Germany are coordinated through Verkehrsverbünde, which contribute immensely to the systems' cost-effectiveness and consumer appeal.